DOI: 10.11606/t.45.2012.tde-26042012-235529
|View full text |Cite
|
Sign up to set email alerts
|

Unidades de ZCpn

Abstract: Unidades de ZC p n Seja C p um grupo cíclico de ordem p, onde pé um número primo tal que S = {−1, θ, 1 + θ, 1+θ +θ 2 , • • • , 1+θ +• • •+θ p−3 2 } gera o grupo das unidades de Z[θ] e θé uma raiz p-ésima primitiva da unidade sobre Q. No artigo "Units of ZC p ", Ferraz apresentou um modo simples de encontrar um conjunto de geradores independentes para o grupo das unidades do anel de grupo ZC p sobre os inteiros. Nós estendemos este resultado para ZC p n , considerando que um conjunto similar a S gera o grupo da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…We have Im f 1 = e 1 × · · · × e l , and we easily verify, using the calculations made to find the set of independent generators of ker 1 that1 − −1 p¯ · x p n−1 −1 is multiplicatively independent with e 1 e 2 · · · e l (the evaluations can be found in [8]). This is a contradiction; therefore, we cannot assume v = −1 p t p n 2p ∈ Im 1 Example 2.…”
Section: Validity Of Hypothesis Of Theoremmentioning
confidence: 66%
“…We have Im f 1 = e 1 × · · · × e l , and we easily verify, using the calculations made to find the set of independent generators of ker 1 that1 − −1 p¯ · x p n−1 −1 is multiplicatively independent with e 1 e 2 · · · e l (the evaluations can be found in [8]). This is a contradiction; therefore, we cannot assume v = −1 p t p n 2p ∈ Im 1 Example 2.…”
Section: Validity Of Hypothesis Of Theoremmentioning
confidence: 66%
“…IL-6 has been classified as a faetor that mainly induces terminal differentiation of B cells and its functional properties are quite different trom those of other B-cell stimulatory factors, sueh as B-cell stimulatory faetor-I/ IL-4 and B-cell growth faetor II/IL-5 [28]. We have previously reported that rheumatoid synovial fluid contained BCDF activity, the molecular weight and functional properties of which are similar to those of IL-6 [19). Houssiau el al.…”
Section: Discussionmentioning
confidence: 99%
“…IgG2b-inducing RA-SF preparations have failed to induce in viiro differeniiation of CESS BCL cells into antibody secretory cells, a property which is believed to be caused by IL-6 [27]. Other authors have also recently described a BCDF activity in the SF of patients with RA, which eould promote the production of RF in vitro [20], but this factor has not been tested on mouse splenic cells.…”
Section: Abedi-valugerdi Ei Atmentioning
confidence: 99%